Analysis of the Implementation of Qanun Aceh No. 7 of 2014 on Employment Social Security in Lhokseumawe City - Muhammad Sulaiman Nasution; Isnaini Isnaini; M. Citra Ramadhan (Borong Newinera Publisher, 2025)
This study analyzes the implementation of Qanun Aceh No. 7 of 2014 on employment social security in Lhokseumawe City. The main focus of this study is to examine the legal rules of BPJS Ketenagakerjaan, analyze the implementation of the qanun, and identify the obstacles faced in its implementation. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation studies. The results of the study show that although the employment social security regulation has a strong legal basis, its implementation in Lhokseumawe City still faces challenges. The level of corporate compliance varies, where large companies have generally fulfilled their obligations, while the small and medium enterprises (SMEs) sector still has many that have not complied with the rules. Workers' awareness of the importance of social security is also still low, especially in the informal sector, which leads to a low level of BPJS Employment participation. The main obstacles in the implementation of this qanun include lack of socialization, weak supervision and sanctions for non-compliant companies, and limited human resources in supervision. To overcome this problem, strategies such as increasing education for employers and workers, stricter law enforcement, and collaboration between the government, BPJS Employment, and employer associations are needed. This study concludes that although Qanun Aceh No. 7 of 2014 has become a strong legal instrument, its implementation still needs to be strengthened so that the benefits of employment social security can be optimally felt by all workers in Lhokseumawe City.